The Effect of Servant Leadership and Trust in Leadership on Organizational Citizenship Behavior with Interpersonal Communication Mediation - Ida Ayu Susilawati,; I Wayan Gede Supartha, (Technium Social Sciences Journal, 2020)
The purpose of this study was to analyze the effect of servant leadership and trust in leadership on interpersonal communication and organizational citizenship behavior (OCB). In addition, this study also aims to analyze the role of interpersonal communication as a mediation on the effect of servant leadership and trust in leadership on OCB among employees at the Faculty of Economics and Business, Udayana University. This study uses an associative approach with a locus at the Faculty of Economics and Business, Udayana University. So that the population of this research is all 122 employees of the Faculty of Economics and Business, University of Udayana, and the sample is taken with saturated sampling technique. Data were collected through a questionnaire and analyzed by path analysis. The results showed that servant leadership and trust in leadership had a positive and significant effect on interpersonal communication. Likewise, servant leadership, trust in leadership, and interpersonal communication also have a positive and significant effect on OCB. Interpersonal communication has also been shown to significantly mediate the effect of servant leadership and trust in leadership on OCB.